Primary healthcare as a strategy for well being in the elderly - Parodi G., José Francisco (2009)
The 21th Century shows marked changes in demographic trends compared to 20th Century. Consequently, now there is an increase in life expectancy and a greater proportion of elderly people. This poses a significant impact on healthcare systems and social security services, as well as on their capability for taking care of a progressively susceptible population, particularly in the context of a new epidemiological scenario which is a consequence of climatic change and globalization.